Design of XYZ Village Poor Household Information System - Nugraha, Ucu; Supriadi, Hari (International Journal of Psychosocial Rehabilitation, 2020)
The manual system for managing community data collection that is currently running is felt to be no longer adequate for handling workloads, especially household data collection. This situation demands immediate use of information systems based on computer technology that aim to better organize data so that the information obtained is more accurate. The existence of this system will also facilitate village officials in compiling reports and graphs on the development of community data in their environment. The method used in making the system information on the collection of poor households is an observation method, an interview method. Whereas in the design of information systems conceptually is system analysis and system design.